Partisipasi Anggaran dan Senjangan Anggaran Dengan Ketidakpastian Karir Sebagai Variabel Pemoderasi - Okayanti, Ni Made Dwi; Dwija Putri, I Gusti Ayu Made Asri (E-Jurnal Akuntansi; Vol 33 No 11 (2023)DO - 10.24843/EJA.2023.v33.i11.p02, 2023)
The aim of this research is to analyze and obtain empirical evidence about the effect of budget participation on budgetary slack which is moderated by career uncertainty. This research was conducted at Regional Government Organizations (OPD) in the form of departments and agencies in Gianyar Regency. The research sample was determined using a purposive sampling method of 108 samples consisting of heads of departments/agencies, secretaries, finance sub-divisions and planning sub-divisions from each OPD. The data collection method used is a survey method with a questionnaire instrument. The data analysis technique used is Moderated Regression Analysis (MRA). The research obtained results that the budget participation variable had a positive effect on budget gaps and the career uncertainty variable weakened the effect of budget participation on budget gaps in the OPD of Gianyar Regency. Keywords: Budgetary Participation; Career Uncertainty; Budgetary Slack